Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5539/mas.v8n4p97
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Fiber Profiles of Cottonseed from Upland Cotton with Different Fertilizations

Abstract: Whole cottonseed and its derived products can be used as human food, animal feed, and industrial raw material. Chemical composition of cottonseed is one of the critical parameters for evaluating its quality and potential end use. Especially, protein and dietary fibers are two desirable nutritional properties of cottonseed for animal feed. In this study, we determined their contents in cottonseed harvested from different fertilization managements with or without wheat cover crop in two consecutive years. Seed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…This observation indicated that the amino acids cysteine (cystine) and/or methionine in protein (He et al, 2014d;Voet & Voet, 1990) were the major S source in the products. Furthermore, a high S content in CSPw than in CSPa and CSPI was consistent with the previous observation that the content of cysteine of CSPa was the highest among the three lab-produced protein fractions (He et al, 2014f). The contents of the micromineral elements were in the general range of cottonseed and meal products (Bellaloui et al, 2015a;Bellaloui & Turley, 2013;He et al, 2013b).…”
Section: Ash and Selected Mineral Element Contentssupporting
confidence: 77%
See 3 more Smart Citations
“…This observation indicated that the amino acids cysteine (cystine) and/or methionine in protein (He et al, 2014d;Voet & Voet, 1990) were the major S source in the products. Furthermore, a high S content in CSPw than in CSPa and CSPI was consistent with the previous observation that the content of cysteine of CSPa was the highest among the three lab-produced protein fractions (He et al, 2014f). The contents of the micromineral elements were in the general range of cottonseed and meal products (Bellaloui et al, 2015a;Bellaloui & Turley, 2013;He et al, 2013b).…”
Section: Ash and Selected Mineral Element Contentssupporting
confidence: 77%
“…The contents of the micromineral elements were in the general range of cottonseed and meal products (Bellaloui et al, 2015a;Bellaloui & Turley, 2013;He et al, 2013b). Similar to those lab-produced products (He et al, 2014f) and due to the nature of micro abundance, the changes of these mineral contents were relatively small, compared to the percentage of the major components and macro elements in the composition of these products. A positive observation was that, without remarkable changes in these micro minerals and other nutrients, CSIR could be used at least as animal feedstuffs as CSM does (Arieli, 1998;Bellaloui et al, 2015b) whereas its industrial utilization need to be explored.…”
Section: Ash and Selected Mineral Element Contentsmentioning
confidence: 58%
See 2 more Smart Citations
“…and carbohydrates, it is not suitable for consumption by human and other monogastric animals due to the presence of toxic gossypol. [2,6] It is currently used as low value fertilizers and feedstuff of ruminant animals. [2,7] Therefore, we have conducted research on the industrial utilization of cottonseed meal as wood adhesives in order to increase the value of the defatted meal fraction.…”
Section: Introductionmentioning
confidence: 99%